Binge eating behavior among a cohort of normal weight college women. Issue 12 (December 2019) - Kells, Meredith; Kelly-Weeder, Susan
ABSTRACT: Background and purpose: Binge eating (BE) has been linked to the development of eating disorders and obesity, and it has been reported in college women. Few studies investigate BE by weight category. The purpose of this study was to examine BE in "normal" weight college women. Methods: Secondary analysis of Web-based survey at a private university in the northeastern United States. Results: Sample was 317 female subjects, 75.4% were White. Binge eating was reported by 99 women (31.2%); 7.6% of binge eaters were underweight, 73.5% normal weight, 15.3% overweight, and 4.1% obese. Normal weight binge eaters were more likely to purge ( x 2 = 6.830; p = .033) and overexercise ( x 2 = 15.179, p = .019). All binge eaters reported feeling sad, guilty, or distressed after eating and weight dissatisfaction. Normal weight binge eaters reported negative affect before ( x 2 = 33.187; p < .001) and after eating ( x 2 = 36.329; p < .001) more frequently than normal weight non–binge eaters. Normal weight binge eaters more often described themselves as overweight when compared with normal weight non–binge eaters ( x 2 = 9.267; p = .026). Implications for practice: Nearly one third of college women report BE, the majority are of normal weight. These women are more likely to engage in compensatory mechanisms and have distorted body image and a negative affective state with eating. Findings highlight the importance of screening for BE in college women regardless of weight.